2002
DOI: 10.1109/lpt.2002.1021966
|View full text |Cite
|
Sign up to set email alerts
|

Temperature sensitivity of 1300-nm InGaAsN quantum-well lasers

Abstract: Abstract-The temperature sensitivity of metal-organic chemical vapor deposition (MOCVD)-grown highly strained (1 2.7%) In 0 4 Ga 0 6 As-and In 0 4 Ga 0 6 As 0 995 N 0 005 quantum-well (QW) active lasers, with lasing wavelength of 1.185 and 1.295 m, respectively, is analyzed in terms of measured fundamental device parameters. From our analysis, the lower 0 values for the InGaAsN QW lasers can be explained in terms of the temperature dependence of the current injection efficiency, presumably due to increased car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
55
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 13 publications
4
55
1
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11][12] Less temperature sensitivity in InGaAsN QW lasers, at ϭ1300 nm, has also been demonstrated in many of the published results. [1][2][3][4][5][6][7][8][9][10][11][12] Although the area of temperature sensitivity in InGaAsN QW lasers is still under extensive investigation, 13,14 promising results of both low threshold-current-density (J th ) and high T 0 values ͓1/T 0 ϭ(1/J th )dJ th /dT͔ have been demonstrated. 3,6,12 Recently, efforts to achieve high performance InGaAsN QW lasers by metalorganic chemical vapor deposition ͑MOCVD͒ 3-7 have been pursued.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][4][5][6][7][8][9][10][11][12] Less temperature sensitivity in InGaAsN QW lasers, at ϭ1300 nm, has also been demonstrated in many of the published results. [1][2][3][4][5][6][7][8][9][10][11][12] Although the area of temperature sensitivity in InGaAsN QW lasers is still under extensive investigation, 13,14 promising results of both low threshold-current-density (J th ) and high T 0 values ͓1/T 0 ϭ(1/J th )dJ th /dT͔ have been demonstrated. 3,6,12 Recently, efforts to achieve high performance InGaAsN QW lasers by metalorganic chemical vapor deposition ͑MOCVD͒ 3-7 have been pursued.…”
mentioning
confidence: 99%
“…4, the g oJ of the InGaAsN QW laser is measured to be 1150 cm Ϫ1 , which is significantly lower that (g oJ ϭ1600-1900 cm Ϫ1 ) of similar InGaAs QW lasers 2 The expected length dependence of T 0 and T 1 is due to the variation of threshold gain with cavity length. 13 In analyzing these T 0 values, one has to consider the fact that high-J th QW lasers with large monomolecular recombination will result in devices with high T 0 values. 13 Relatively low T 0 values for low-J th InGaAsN QW lasers can result from carrier leakage, 13 temperature-sensitive gain, 13 and/or Auger recombination.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some recent works 14 have attributed the poor T 0 values in 1300 nm InGaAsN QW lasers to the existence of large Auger recombination processes. Other recent work 15 has identified that increased carrier leakage processes and a more temperature sensitive material gain parameter play a pivotal role in leading to increased temperature sensitivity of 1300 nm InGaAsN QW lasers.…”
mentioning
confidence: 99%
“…Without employing a growth pause before and after the InGaAsN QW, no luminescence intensity was measured from structures with direct barriers of GaAs 0.85 P 0. 15 . By incorporating a pause of approximately 10 and 15 s before and after the growth of the InGaAsN QW, respectively, a significant improvement in luminescence of the InGaAsN-GaAsP structure is observed with a wavelength emission of 1.26 -1.275 m as shown in Fig.…”
mentioning
confidence: 99%